Life experiences associated with change in perpetration of domestic violence - Avanti Adhia; Vivian H. Lyons; Hannah Cohen-Cline; Ali Rowhani-Rahbar (BMC, 2020)
Abstract Background This study assessed whether several adult life experiences, including loss of support, loss of food security, loss of housing, and substance use cessation, are associated with change in domestic violence (DV) perpetration from early to later adulthood. Using 2015 to 2016 cross-sectional, self-report survey data from Medicaid enrollees in Oregon (N = 1620), we assessed change in DV perpetration from early adulthood (19-30 years) to later adulthood (≥ 31 years of age), cut points determined by existing survey questions. Multinomial logistic regression models were constructed to estimate the association between life experiences and physical DV perpetration using odds ratios (OR), adjusting for sociodemographic characteristics, DV victimization, and childhood abuse, bullying, and social support. Findings Of the 20% of participants who perpetrated DV, 36% perpetrated DV in both early and later adulthood (persisters), 42% discontinued (desisters) and 22% began (late-onsetters) perpetration in later adulthood. Loss of support and loss of food security were both associated with change in DV perpetration (i.e., desistance or late onset of perpetration or both). Loss of support was associated with 9.5 times higher odds of being a desister (OR = 9.5, 95% CI = 1.1, 84.1) and 54.2 times higher odds of being a late-onsetter (OR = 54.2, 95% CI = 6.5, 450.8) of DV perpetration compared to persisters. Loss of food security was associated with 10.3 times higher odds of being a late-onsetter (OR = 10.3, 95% CI = 1.9, 55.4) of DV perpetration compared to persisters. In addition, substance use cessation was associated with 10.3 times higher odds of being a desister (OR = 10.3, 95% CI = 1.9, 56.2) compared to persisters. Conclusions Findings suggest that specific life experiences in adulthood, including loss of support, loss of food security, and substance use cessation, are associated with changes in DV perpetration.